2021
DOI: 10.1177/17562848211004839
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis: the impact of co-occurring immune-mediated inflammatory diseases on the disease localization and behavior of Crohn’s disease

Abstract: Background: Patients with Crohn’s disease (CD) are at increased risk of co-occurring immune-mediated inflammatory diseases (IMIDs). As discrepancy exists regarding the phenotypic presentation of CD among patients with such co-occurring IMIDs, we aimed to conduct a systematic review with meta-analysis characterizing the phenotype of CD among this subgroup of patients. Methods: PubMed, Embase, and Scopus were searched from their earliest records to October 2019 for studies reporting the behavior and localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…Another recent systematic review and meta-analysis found that CD patients with concurrent IMIDs were more likely to have upper gastrointestinal involvement and nonstricturing and nonpenetrating phenotypes than those without IMIDs. Given that this meta-analysis suggests that CD patients with concurrent IMIDs may have a milder disease course, which contradicts the findings of the previous meta-analysis, more research is needed to better understand CD patients’ behaviors if they develop other IMIDs and require medication[ 35 ].…”
Section: Imids Affecting Ibd Phenotypes and Outcomesmentioning
confidence: 92%
See 2 more Smart Citations
“…Another recent systematic review and meta-analysis found that CD patients with concurrent IMIDs were more likely to have upper gastrointestinal involvement and nonstricturing and nonpenetrating phenotypes than those without IMIDs. Given that this meta-analysis suggests that CD patients with concurrent IMIDs may have a milder disease course, which contradicts the findings of the previous meta-analysis, more research is needed to better understand CD patients’ behaviors if they develop other IMIDs and require medication[ 35 ].…”
Section: Imids Affecting Ibd Phenotypes and Outcomesmentioning
confidence: 92%
“…Patients with “extensive UC” had a higher prevalence of PSC than those with left-sided colitis. PSC was more common in CD patients with ileocolonic or colonic involvement than in those with ileal involvement[ 35 , 41 ]. PSC-IBD patients have a predilection for more severe right-sided colitis according to several studies[ 42 , 43 ].…”
Section: Imids Affecting Ibd Phenotypes and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation